Genome mining of secondary metabolites from marine Streptomyces spp. as potent therapeutics for RET-specific non small-cell lung cancer - Gurmuras, Rhydhy Rasika; Krishnamoorthy, HemaNandini Rajendran; Karuppasamy, Ramanathan (Intelektual Pustaka Media Utama, 2025)
The rearranged during transfection (RET) gene encodes a tyrosine kinase oncogene implicated in various cancers, including non-small-cell lung cancer (NSCLC). Till now, multiple kinase inhibitors are commonly used to treat RET-positive NSCLC. However, these inhibitors often exhibit significant toxicity and demonstrate reduced efficacy and specificity toward RET. Recently, bioactive compounds derived from marine sources have shown promising anticancer properties. Therefore, this study aimed to identify effective bioactive compounds from marine Streptomyces species using a virtual screening approach to address these limitations. A literature search identified 20 marine Streptomyces species as potential sources of bioactive compounds. The antibiotics and secondary metabolite analysis shell (antiSMASH) online tool were used to analyze the gene clusters of these marine Streptomyces species, revealing 7,251 metabolites. A total of 661 distinct metabolites were analyzed through a comprehensive array of virtual screening methodologies. The molecular docking and pharmacokinetic analysis resulted in the identification of four metabolites with better binding scores and pharmacological properties than pralsetinib. Collectively, we hypothesize that the identified bioactive compounds could be considered as potent leads for further analysis.